Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3155/1047-3289.59.9.1049
|View full text |Cite
|
Sign up to set email alerts
|

Using High Time Resolution Aerosol and Number Size Distribution Measurements to Estimate Atmospheric Extinction

Abstract: Rocky Mountain National Park is experiencing reduced visibility and changes in ecosystem function due to increasing levels of oxidized and reduced nitrogen. The Rocky Mountain Atmospheric Nitrogen and Sulfur (Ro-MANS) study was initiated to better understand the origins of sulfur and nitrogen species as well as the complex chemistry occurring during transport from source to receptor. As part of the study, a monitoring program was initiated for two 1-month time periods-one during the spring and the other during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Previous studies based on field measurements and laboratory experiments have shown that the composition of submicron particles is dominated by Org, followed by NO 3 − , NH 4 + , and SO 4 2− . The contributions of Cl − and dust are negligible (Levin et al., 2014; Malm et al., 2009; Whitby, 1978; F. Zhang et al., 2014). Therefore, only Org, ammonium nitrate (NH 4 NO 3 ), sulfuric acid (H 2 SO 4 ), ammonium sulfate [(NH 4 ) 2 SO 4 ], ammonium hydrogen sulfate (NH 4 HSO 4 ), and BC were considered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies based on field measurements and laboratory experiments have shown that the composition of submicron particles is dominated by Org, followed by NO 3 − , NH 4 + , and SO 4 2− . The contributions of Cl − and dust are negligible (Levin et al., 2014; Malm et al., 2009; Whitby, 1978; F. Zhang et al., 2014). Therefore, only Org, ammonium nitrate (NH 4 NO 3 ), sulfuric acid (H 2 SO 4 ), ammonium sulfate [(NH 4 ) 2 SO 4 ], ammonium hydrogen sulfate (NH 4 HSO 4 ), and BC were considered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…From alpine meadows to stark peaks, Rocky Mountain National Park (RMNP) hosts abundant wildlife, an important water catchment, and roughly 3 million visitors per year (Annual Park Visitation Report, NPS Public Use Statistics Office). Recent studies chronicle visibility reduction in RMNP, a Clean Air Act Class I protected environment, due to fine particles, especially in the summer when concentrations are higher (Levin et al, 2009;Malm et al, 2009b). Environmental impacts from increased nutrient -and particularly nitrogen -deposition are also documented in the Colorado Rocky Mountains (Baron et al, 2000), where mountainvalley circulations periodically transport ammonium, nitrate, and other particulate species from agricultural and urban sources to the east (Benedict et al, 2013a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, PILS has been coupled with ion chromatography, allowing for quantitative measurements of common atmospheric water-soluble inorganic ions and several small carboxylic acids in ambient and lab generated aerosols. More recent applications include PILS coupled to an online total organic carbon analyzer for measurements of the total WSOC content; , PILS coupled to a liquid waveguide capillary cell and absorption spectrometer for detection of water-soluble iron in atmospheric aerosols; and PILS coupled to offline ESI-MS, gas chromatography/mass spectrometry (GC/MS), or liquid chromatography/mass spectrometry (LC/MS) measurements. , …”
mentioning
confidence: 99%